Does exercise enhance the benefits of nutritional support on the biochemical markers of nutrition, anthropometry, and body composition in hemodialysis patients? A systematic review - Kamalzadeh Yazdi, Raheleh; Radkhah, Nima; Ostadrahimi, Alireza (Frontiers in Nutrition, 2024)
Exercise and nutritional support are effective strategies in hemodialysis patients who often face health issues like protein-energy wasting (PEW). Therefore, this study aimed to evaluate whether combining exercise with nutritional support offers additional benefits for anthropometry, body composition, and biochemical markers of nutrition in hemodialysis patients.This systematic review searched databases, including PubMed, Scopus, and Web of Science, until 14 February 2024 to identify relevant randomized controlled trials. Following screening and data extraction, quality assessment was conducted using the revised Cochrane Risk of Bias tool (ROB2). The study was reported following PRISMA guidelines.Six studies comprising 199 male and female hemodialysis patients were included. These studies did not report any significant differences in anthropometry, body composition, and nutritional status between individuals who received an exercise program along with nutritional support and those who received only nutritional support.This systematic review suggests that the combination of exercise with nutritional support may not improve the positive effects of nutritional support on anthropometry, body composition, and nutritional status in hemodialysis patients. However, due to the low quality and significant heterogeneity among the existing studies, further research is required to draw definitive conclusions.